محاذير كتابة المصحف الشريف بالرسم الإملائي - مقراني، عادل Muqrani, Adel (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست - معهد الآداب واللغات, 2015)
[ In this research ,I have tackled the precautions of writing in the holy book (the Quran).These precautions are linked to various sides, among which those that connected to the history of writing the Quran from the view of its relevance, history of writing and recording it; and those that are connected to its language, from the angle of the extinction of some languages, the breaking of followers ‘guidance (God be pleased with them). Moreover, other precautions concern the way the Quran is taught (its learning by heart and its teaching), breaking of the approaches of the priests and leaders in their teaching the Quran and its different readings to students. Finally, I have mentioned the precautions that are related to the understanding and contrive of Quran.]
تحدثت في هذا البحث عن محاذير كتابة المصحف الشريف بالرسم الإملائي؛ والتي تتصل بجوانب متعددة، فمنها ما يتعلق بتاريخ كتابة المصحف الشريف، من جانب وثاقته، وتاريخ كتابته وتدوينه، ومنها ما يتصل بلغته، من ناحية اندثار بعض لغات العرب، ومخالفة هدي الصحابة، ومنها ما يرتبط بطريقة تلقين القرآن الكريم، من جهة حفظه وتحفيظه، ومن جهة مخالفة منهج القراء والأئمة في تلقينهم الطلاب للقرآن والقراءات القرآنية، وختمت هذه المحاذير بالتطرق للمحاذير المتعلقة بفهم القرآن وتدبره.
Keywords: القرآن الكريم -- المصحف الشريف -- الرسم الإملائي -- اللغة العربية -- القراءات القرآنية